ANALISIS NILAI TAMBAH DAN INDEX DIVERSIFIKASI AGROINDUSTRI PANGAN LOKAL ENBAL UBIKAYU - Timisela, Natelda R (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The aim of this research is to analyze the added value and diversification index as well as the factors that influence the level of product diversification. The research was conducted in Southeast Maluku Regency. The research sample is cassava enbal agroindustry actors. The results showed that the ratio of added value and profit for agro-industry actors was 26.15% and 25.88%. The average cassava agroindustry entropy index is 1.31, the highest index is 1.79 and the lowest index is 1.04. This value means that the cassava agro-industry diversifies processed products, but it is not maximized. The results of the analysis simultaneously with the F-test are shown in Table 1. The calculated F-value of 28.72 is greater than the F-table of 2.10. This means that together the length of business, business capital, education level, availability of labor, age of craftsmen, number of family members and dummy income of agro-industry and non-agro-industry have a significant effect on the level of product diversification.